2020
DOI: 10.1002/jia2.25613
|View full text |Cite
|
Sign up to set email alerts
|

Successes and gaps in the HIV cascade of care of a high HIV prevalence setting in Zimbabwe: a population‐based survey

Abstract: Introduction: Gutu, a rural district in Zimbabwe, has been implementing comprehensive HIV care with the support of M edecins Sans Fronti eres (MSF) since 2011, decentralizing testing and treatment services to all rural healthcare facilities. We evaluated HIV prevalence, incidence and the cascade of care, in Gutu District five years after MSF began its activities. Methods: A cross-sectional study was implemented between September and December 2016. Using multistage cluster sampling, individuals aged ≥15 years l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 22 publications
1
27
0
4
Order By: Relevance
“…When restricting to the age group 15-64 years, HIV prevalence was 13% in our survey versus 16% in the southwest zone where Nsanje District is located [1]. As documented in other settings, women were more likely to be infected with HIV than men [14][15][16][17].…”
Section: Discussionmentioning
confidence: 76%
“…When restricting to the age group 15-64 years, HIV prevalence was 13% in our survey versus 16% in the southwest zone where Nsanje District is located [1]. As documented in other settings, women were more likely to be infected with HIV than men [14][15][16][17].…”
Section: Discussionmentioning
confidence: 76%
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies reported numbers or percentages of patients retained at this step [8,20‐32,34,36,40‐43,46,56,58,65,68,69,72‐74,76‐93,95‐99]. The majority of studies (32 studies, 62%) covering this step were longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations